(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Pollen morphology of 11 taxa, including 2 endemic of the genus Aethionema W.T. Aiton from Turkey was examined under light and scanning electron microscopes. The pollens of Aethionema are mostly isopolar and bilaterally symmetric; spheroidal, prolate, perprolate and subprolate with the polar axes 14.07-26.41 μm and the equatorial axes 7.85-22.02 μm; mostly tricolpate, rarely 2-colpate; surface ornamentation is micro or macro reticulate. The exine thickness varies between 0.66 and 1.91 μm, and in tine thickness ranges from 0.27 to 0.85 μm. It is found that dimension of pollen grains, surface ornamentation, apocolpidium and amb diameter are taxonomically significant. Bangladesh J. Plant Taxon. 24(2): 197-204.